Evaluating Business Modeling Tools from a Creativity Support System Perspective – Results from a Focus Group in the Software Development Industry - Voigt, Matthias; Plattfaut, Ralf; Ortbach, Kevin; Malsbender, Andrea; Niehaves, Björn; Becker, Jörg (Pacific Asia Conference on Information Systems (PACIS), 2013)
Business modeling tools provide IT support in the complex process of business modeling. Little research exists on the evaluation of business modeling tools. We interpret business modeling as a creative process and evaluate a specific business modeling tool (OctoProz) by assessing its potential for fostering creative performance. We draw on literature on the design of creativity support systems, that is, the components for collaborative idea development, and position our business modeling tool as a creativity support system. We conduct a focus group study in the software development industry, collecting qualitative data on creativity-specific tool properties of OctoProz: playfulness, comprehension, specialization, and collaboration. The results show that task-specificity of the tool was highly appreciated by the business modeling experts, while improvements are needed with regards to playful interaction with the business model and support of comprehension of the business model. Real-time collaboration in the modeling process over-satisfies the experts’ needs. Our findings contribute to the purposeful design of business modeling tools. Further, the results suggest that the components for collaborative idea development are valid, while aspects of GUI design and collaboration modes require further attention. We finally indicate limitations and future research directions.